Una nueva aproximación al Problema de Balanceo de Currículo Académico - Lopes, Clayton Brás de Souza (2023)
Academic Curriculum Balancing is an alternative for building curricular paths, with a focus on planning the student's workload, by assigning subjects to periods in a balanced way in relation to the number of credits and respecting the prerequisites. This work presents the development of a multi-objective model entitled Balancing Academic Curriculum with Subjects Failure Data, which has three objectives: distribute credits more evenly between periods, bring interrelated disciplines closer and more adequately balance disciplines with high retention. The model was transcribed using an exact Mixed Quadratic Integer Programming and Constraint Programming, and given its multi-objective feature, the Weighted Sum method was applied in the achievement of the solutions, constituted in the Pareto frontier. The experimental results obtained by tests in a higher education curriculum provided significant improvements in the balance of student workload. A computational tool that encompasses the new model was developed, in order to enable the application of the proposed approach in real scenarios, favoring learning and completion of the course in the ideal time. In an survey carried out with students and managers, the fulfillment of the objectives of tool and its applicability remained demonstrated.